Nomogram for Predicting Risk of Esophagogastric Junction (EGJ) Resection During Laparoscopic Resection of Gastrointestinal Stromal Tumors in EGJ: A Retrospective Multicenter Study - Xu, Yuting; Luo, Lijie; Feng, Xingyu; Zheng, Yensheng; Chen, Tao; Zhou, Rui; Li, Yong; Li, Guoxin; Wang, Wei; Xiong, Wenjun (Frontiers in Surgery, 2021)
Abstract Background: The established criteria for determining whether to excise the cardia during laparoscopic surgery for gastrointestinal stromal tumors in the esophagogastric junction (EGJ-GISTs) remain controversial. This retrospective multicenter study was conducted to develop a nomogram for predicting the risk of the cardia excision during laparoscopic surgery for EGJ-GISTs. Material and methods: We reviewed data from 2127 gastric-GISTs (g-GISTs) patients without distant metastases in four hospital between June 2012 and June 2020. Of those, according to the including criteria, 184 patients (Guangdong Provincial Hospital of Chinese Medicine (n=81), Nanfang Hospital of Southern Medical University (n=60), Guangdong General Hospital (n=34), and The Third Affiliated Hospital of Southern Medical University (n=9)) with EGJ-GISTs were identified and included in this study. Factors contributing to risk of cardia excision were identified and used to create a nomogram. Nomogram performance was assessed using a bootstrapped concordance index (c-index) and calibration plots. Results: According to the multivariate analysis, the distance from the margin of the tumor to the esophagogastric line (EG-line) (cm) (OR=0.001, 95% CI: 0.000010.056, P=0.001) and tumor size (cm) (OR=14.969, 95% CI: 1.876119.410, P=0.011) were significantly related to likelihood of cardia structure excision in laparoscopic surgery for EGJ-GISTs. These two factors were used to generate a nomogram for predicting risk of cardia excision using a logistic regression model; a bootstrapped C-index of 0.988 (calibrated C-index=0.987) indicated strong predictive ability, with broad calibration. Conclusions: This nomogram based on distance from tumor margin to EG-line and tumor size may serve as a tool for predicting risk of cardia damage during laparoscopic removal of EGJ-GISTs to aid in selection of surgical methods and preoperative neoadjuvant therapy.